Chapter La bioregione urbana, strumento multidisciplinare del progetto eco-territorialista - Magnaghi, Alberto (Territori, 2023)
The spread of pandemics, war and the climate crisis has shown how close the unsustainability of the current development model, oblivious of places and their inhabitants, has now come to a point of no return; but at the same time it has made more transparent - as well as more urgent - the reasons for the eco-territorialist turn, centred on the conceptual and operational device of the urban bioregion. Delving into a discussion already underway, the essay describes such a tool by declining it along three analysis and design axes: the founding role of territorial heritage, the integrated and synergic activation of all the "constructive elements" of the production of space, and the self-government of the territory as a common good.